2016
DOI: 10.20944/preprints201610.0060.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Soft Tissue Pathophysiology in the Development and Maintenance of Bisphosphonate Related Osteonecrosis of the Jaw (BRONJ)

Abstract: Abstract:Since the first description of bisphosphonate-related osteonecrosis of the jaw (BRONJ) numerous research groups have focused on possible pathological mechanisms including the suppression of the bone turnover of the jaw, antiangiogenic effects and soft tissue toxicity. In our review we focused on summarizing the role of the soft tissues in the development and progression of BRONJ. The biological behavior of fibroblasts can be significantly influenced by bisphosphonates (BP) such as a concentration depe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Compared with the Exp + Saline group, treatment with BBG after tooth extraction effectively reduced the occurrence of BRONJ and promoted tissue healing in the extraction sockets. Recent studies indicated that soft tissue covering is a key factor for preventing BRONJ by mitigating secondary contamination and re‐establishing vascularized tissues (Ziebart et al., 2016). After BBG administration, inflammation at the injured site was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the Exp + Saline group, treatment with BBG after tooth extraction effectively reduced the occurrence of BRONJ and promoted tissue healing in the extraction sockets. Recent studies indicated that soft tissue covering is a key factor for preventing BRONJ by mitigating secondary contamination and re‐establishing vascularized tissues (Ziebart et al., 2016). After BBG administration, inflammation at the injured site was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have suggested that BPs stimulate the production of osteoprotegerin, an osteoclast differentiation inhibitor in osteoblasts, and inhibit osteoclast differentiation 3,6) . Moreover, BPs are known to affect fibroblasts and vascular endothelial cells [7][8][9][10][11] ; however, there are few detailed studies regarding the mechanism of BPs involved in soft-tissue healing. Therefore, the effects of zoledronic acid (ZOL) on human gingival fibroblasts (HGFs) and human umbilical vein endothelial cells (HUVECs) were evaluated in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced number and function of monocytes and macrophages caused by repeated administration of BPs could induce local immune dysfunction, infection, and necrosis involved in ONJ (Pazianas, 2011). In addition, as farnesyl pyrophosphate synthase (FPPS) inhibitor, nitrogen‐containing BPs especially ZOL possess worse effects on cell biology than non‐nitrogen‐containing BPs by blocking the mevalonate pathway (Ziebart et al., 2016). Considering that the macrophages RAW 264.7 can differentiate into multinucleated osteoclasts after RANKL stimulation, they are used as model of osteoclast precursors (Odkhuu et al., 2012).…”
Section: Introductionmentioning
confidence: 99%